Sustainability as source of competitive advantages in mature sectors: The case of Ceramic District of Sassuolo (Italy). Issue 1 (1st April 2019) - Settembre Blundo, Davide; García-Muiña, Fernando Enrique; Pini, Martina; Volpi, Lucrezia; Siligardi, Cristina; Ferrari, Anna Maria
Abstract : Purpose: The purpose of this paper is to explore how sustainability can become a source of competitive advantage for mature manufacturing sectors where technologies are standardized, and innovation is mainly generated across the value chain and not by individual companies. Design/methodology/approach: From the methodological point of view, this research estimates the sustainability status of ceramic production in the Sassuolo district (Italy), using the Life Cycle Sustainability Assessment (LCSA) model, and changing the observation point for the analysis, from the enterprise (micro level) to the entire sector (meso level). Findings: This paper provides an analysis of the environmental, economic and social impacts of the four main types of ceramic tiles manufactured in Italy, both in aggregate terms for the entire sector and per square meter of product. Practical implications: The methodological approach used in this research is easy to replicate both for companies when designing their sustainability strategies and for public decision makers when assessing the sustainability performance of a sector or supply chain. Social implications: For the first time, a socio-economic impact assessment is proposed for the ceramic sector, conducted in parallel with the environmental impact assessment through stakeholder mapping and prioritization. Originality/value: This paper conceptualizes the theme of relations and interdependencies between ceramic producers organized in industrial districts and the territories in which they operate in order to determine empirically the sustainability performance of Italian ceramic sector, using the LCSA model with a territorial extension that presupposes an innovative contribution to current literature and practice.